Perancangan Sistem Informasi Persediaan Stok Barang Dan Penjualan Pada Toko Raja Sosis Menggunakan Bahasa Pemrograman PHP Dan Database MySQL - Safitri, Mesa; Marfalino, Hari (Riset Sinergi Indonesia, 2023)
E-commerce as a means of selling frozen food at the King Sausage shop, because it is considered to save time and energy so it is more effective and efficient, there is no need to queue and just wait for the goods ordered to arrive at the buyer's place without having to leave the house just by using connection and internet and assist employees in processing sales transactions. uses the EOQ (Economic Order Quantity) method to determine the economic quantity for each order so as to minimize the total cost of inventory at the sausage king shop. It is hoped that the information system for stock inventory and sales at the King Sausage shop will provide maintenance and development for this system so that it can be used sustainably as long as it is needed.